The Phenomenon of Homosexuality Between Divine Religions and International Organizations - Belqis Al-Murakeb (Maklumat: Journal of Da'wah and Islamic Studies, 2024)
This text examines the global spread of homosexuality, including in Arab and Islamic societies, aiming to clarify its concept, causes, and history, while focusing on religious and social perspectives. The research warns against the dangers this phenomenon poses to religious and moral values and calls for deterrent actions. It follows a descriptive, analytical, historical, and critical approach to study and analyze the issue. The findings suggest that all divine religions condemn homosexuality, although some religious groups have deviated and accepted it. The research highlights organized efforts to undermine human values by promoting immoral behaviors and using euphemisms like "homosexuality" instead of "sodomy." It also warns of the pressure applied on nations to accept homosexuality under the guise of tolerance and the support given to homosexuals to encourage their behavior.